Graphical Representations of Kinematical Concepts: A Comparison of Teaching Strategies - Guidugli, Silvina Patricia (2005)
Student difficulties with kinematics concepts and their representations by linear graphs are well known. Several specific learning difficulties have been identified and reported, mainly from studies at the introductory university physics level.1–4 In this paper we investigate the effectiveness of active learning strategies versus traditional instruction on the development of student understanding of kinematical concepts, and their graphical representations, by high school students. We also examine the retention of acquired kinematic concepts and whether it might be affected by subsequent (traditional) instruction.